Engaging Students in Higher Education through Mobile Learning - MENKHOFF, Thomas (Institutional Knowledge at Singapore Management University, 2010)
This exploratory study reports pedagogical experiences with using mobiles phone, wikis and other mobile learning approaches such as walking tours as educational tools in the context of an undergraduate course on Chinese entrepreneurship taught at a university in Singapore. Conceptualised as mobile learning, the paper argues that ICT (information and communication technologies) devices used by students as part of their everyday life such as hand phones in combination with social media such as course wikis and other pedagogical methods such as mini lectures, field visits and walking tours can greatly enrich learners’ experience provided their usage is easy and effectively integrated into the respective instructional strategy.